Program Implementation as Predictor of Students' Performance in Technical Vocational Education - Elaine Rose G. Nachon (Philippine Association of Institutions for Research, Inc., 2016)
The ultimate goal of any institution has always been to produce quality outcomes and create sound impact.  The study is a descriptive evaluation of the Operational Management of Technical-Vocational High School in Laguna, Philippines. Data were obtained from 270 graduates conveniently chosen; 88 randomly selected students; complete enumeration of 61 teaching and non-teaching staff from a public technical vocational high school in Laguna, Philippines; and complete enumeration of 27 workers from the school's partner industries within its geographic location. Documentary analysis, SWOT analysis, and unstructured interviews were used to support quantitative data. Program implementation either taken singly or in combination with student development services appeared to be a highly significant predictor of students' performance in TVE but not of their performance in on-the-job training.  It further revealed that each area thrust in the implementation of the TVE curriculum has strengths and opportunities that reduce its vulnerability to external threats. The study concludes that program implementation affects students' performance in TVE since it includes activities meant to deepen understanding of important concepts and to provide experiential learning for students.